Multifunctional silicone rubber/paraffin@PbWO4 phase‐change composites for thermoregulation and gamma radiation shielding. (28th April 2020) - Lou, Lan; He, Zhiyu; Li, Yingjun; Li, Yongsheng; Zhou, Yuanlin; Lin, Congmei; Yang, Zhijian; Fan, Jinghui; Zhang, Kai; Yang, Wenbin
Summary: A new type of silicone rubber (SR)‐based gamma radiation shielding and thermal regulation composite was developed with paraffin (Pn) @lead tungstate (PWO) phase‐change microcapsules as functional fillers. These SR/Pn@PWO composites have a PWO component that not only exhibits excellent photon attenuation but also can provide a barrier to the molten phase‐change material core. The thermal and mechanical properties of the composites were characterized by differential scanning calorimetry, thermal regulation experiment and mechanical tests. Thermal analysis indicated that the SR/Pn@PWO composites not only reveal reliable energy storage performance which can reach to 52.72 J g −1 enthalpy values but also exhibit good thermal durability. In addition, SR/Pn@PWO composites have enhanced mechanical properties and excellent thermoregulation performance. And the more microcapsules content, the more significant enhancement effect is. A high‐purity germanium gamma spectrometer to measure the attenuation coefficient of the composites for gamma radiation showed that the SR/Pn@PWO composites have good γ‐ray‐shielding property, which increased with the increase of the microcapsules content. Abstract : A sort of silicone rubber (SR)‐based γ‐rays shielding and thermal regulation composite was developed. These composites were prepared by using Pn@PbWO4 microcapsules as functional fillers. These composites exhibited good performance in thermal energy storage. The leakage prevention capability of PCMs was enhanced due to the PbWO4 shell and SR.